2021
DOI: 10.1111/jora.12665
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian and Roma Adolescents’ Perspectives on Their Developmental Assets in Albania During the COVID‐19 Pandemic

Abstract: This mixed‐method study explores the accessibility of developmental assets among Egyptian and Roma minority youth in Albania during the COVID‐19 pandemic. Six focus groups were conducted in August 2020 with Egyptian ( n = 16) and Roma ( n = 15) adolescents (14–20 years, M age = 16.71; SD age = 2.00; 14 girls and 17 boys). In addition, adolescents rated how much they experienced each development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…For example, Miconi et al. ( 2021 ) showed that minority youth in Albania have diminished awareness of and access to resources and developmental assets (lack of money, clothes, or support), as well as greater mental health concerns, with the pandemic as compared with their peers. Thus, the long‐term impact of the pandemic will include varying degrees of continued disruptions in the lives of adolescents as some rebound and recover while others struggle to do so.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Miconi et al. ( 2021 ) showed that minority youth in Albania have diminished awareness of and access to resources and developmental assets (lack of money, clothes, or support), as well as greater mental health concerns, with the pandemic as compared with their peers. Thus, the long‐term impact of the pandemic will include varying degrees of continued disruptions in the lives of adolescents as some rebound and recover while others struggle to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents experiencing the negative effects of the pandemic often were already more at risk before the pandemic, because of individual characteristics such as ineffective coping or emotion regulation strategies, relational factors such as low family or peer support, or contextual factors such as low SES or minority status. Of concern is that for a substantial group of adolescents, risk factors might cluster (Fegert, Vitiello, Plener, & Clemens, 2020 ), resulting in cumulating and cascading effects of the pandemic across multiple interrelated aspects of adolescents’ lives (Miconi et al., 2021 ). As these adolescents are also less likely to have individual, family, or community resources to deal with these negative consequences, they might be more likely to experience negative outcomes across multiple domains of functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adolescents who reported more negative changes reported stronger increases in depressive symptoms (Hollenstein et al., 2021 ), and specific living arrangements, pandemic‐related stressor accumulation, and a lack of adaptive coping strategies were associated with during‐pandemic self‐injury and domestic violence (Steinhoff et al., 2021 ). Also, experiences of discrimination and marginalization and lack of resources were related to mental health problems during the pandemic (Miconi et al., 2021 ).…”
Section: Heterogeneity Of the Impact Of The Pandemic On Adolescent Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, young people living in low-and middle-income countries (LAMICs) often have fewer opportunities and resources to achieve their goals, given the precarious situation and limits on socioeconomic development in many countries (United Nations World Youth Report, 2020). For example, in a study of Egyptian and Roma adolescents living in Albania, participants perceived an overall low availability of developmental assets, which in turn was viewed as posing additional challenges to participants' development (Miconi et al, 2021). Lack of developmental assets was particularly evident during the time period in which this study was conducted, namely during the Covid-19 pandemic, which was viewed as compounding pre-existing structural issues such as high unemployment and discrimination, and local challenges experienced by participants such as violence in their neighbourhoods and/or schools (Miconi et al, 2021).…”
Section: What Does It Mean To Thrive?mentioning
confidence: 99%